2022
DOI: 10.1039/d2nj02797f
|View full text |Cite
|
Sign up to set email alerts
|

Core–shell Co@CoO catalysts for the hydroformylation of olefins

Abstract: A new strategy has been proposed for synthesizing Co@CoO core-shell nanoparticles with a core-shell structure, which involves a facile solvent-thermal process in deep eutectic solvents (DESs). In contrast to irregular...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 58 publications
0
13
0
Order By: Relevance
“…Copyright 2020 Elsevier, Ltd. Panels e and f were reproduced with permission from ref . Copyright 2022 Royal Society of Chemistry.…”
Section: Research Progress For Heterogeneous Hydroformylation By Coba...mentioning
confidence: 99%
See 3 more Smart Citations
“…Copyright 2020 Elsevier, Ltd. Panels e and f were reproduced with permission from ref . Copyright 2022 Royal Society of Chemistry.…”
Section: Research Progress For Heterogeneous Hydroformylation By Coba...mentioning
confidence: 99%
“…On the basis of the above studies, it can be found that the high specific surface area of the support may also promote the dispersion of Co. Xu et al used deep eutectic solvents (DESs) as structural guides to synthesize Co@CoO core–shell NPs with a higher specific surface area compared to aqueous media (Figure a). The catalyst enables the exposure of more active sites, which promotes the efficient utilization of the active species.…”
Section: Enhanced Strategies For the Activity Of Cobalt-based Catalys...mentioning
confidence: 99%
See 2 more Smart Citations
“…Stabilization of the Co complexes with phosphine ligands can improve the stability at the expense of the activity. , In this case, homogeneous Co-based catalysts which were initially applied in the hydroformylation industry have been fastly replaced by homogeneous Rh-based catalysts. , Moreover, approaches of recycling Co are less effective than the mature methods of recycling Rh . To this end, great efforts have been made to directly develop efficient heterogeneous Co-based catalysts. For instance, the Co–Co 2 C interface where Co and Co 2 C adsorbed olefins and CO, respectively, worked in synergy to catalyze the hydroformylation of 1-hexene . Mo 6 C 2 -bonded Co species served as active sites for propene hydroformylation.…”
mentioning
confidence: 99%